Dari Desakralisasi Pengetahuan menuju Etika Ekologis: Integrasi Rasionalitas dan Spiritualitas Seyyed Hossein Nasr - Fatmawati Siti Sa'adah; Mulyadhi Kartanegara; Muslih Muslih (Paradigma: Jurnal Kalam dan Filsafat, 2026)
This article examines the integration of rationality and spirituality in Seyyed Hossein Nasr’s thought and its contribution to ecological ethics. This library-based study employs critical conceptual analysis of Nasr’s principal works on knowledge and the environment. The findings show that reducing intellect to instrumental reason leads to the desacralization of knowledge, the objectification of nature, and ecological exploitation. As an alternative, Nasr proposes scientia sacra, which integrates empirical reasoning, intellect, revelation, and metaphysics. This article argues that such integration is not merely a synthesis of rational and spiritual knowledge but an epistemological reconstruction that transforms nature from a material object into a theophany, or manifestation of divine signs. This reconstruction grounds an ecological ethics that positions human beings as guardians of the cosmic order rather than absolute masters of nature.